Lapsyn controls branch extension and positioning of astrocyte-like glia in the Drosophila optic lobe - Benjamin Richier (Nature Portfolio, 2017)
How glial cells, such as astrocytes, acquire their characteristic morphology during development is poorly understood. Here the authors describe the morphogenesis of astrocyte-like glia in the Drosophila optic lobe, and through a RNAi screen, they identify a transmembrane LRR protein–Lapsyn–that plays a critical role in this process.